2021
DOI: 10.1021/acs.iecr.1c02819
|View full text |Cite
|
Sign up to set email alerts
|

Capsules of the Poly(α-olefin) PAO432 for Removal of BTEX Contaminants from Water

Abstract: Poly­(α-olefins) (PAOs) are nonvolatile and nontoxic liquid hydrocarbon oligomeric solvents with solubility properties similar to heptane. PAOs can be used in traditional liquid–liquid extractions, but handling difficulties arise due to the formation of emulsions. In this study, PAO432, a low viscosity PAO with a molar mass of 432 g/mol, is encapsulated in a polymer-based shell using a Pickering emulsion stabilized by graphene oxide nanosheets and interfacial polymerization. The capsules are spherical with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…GO was selected because of previous work demonstrating its effectiveness for stabilizing oil-in-water emulsions. [20][21][22][23][24] Optical microscopy images of the emulsion before polymerization are provided in Fig. S1 † and demonstrate that the interface between the dispersed and continuous phases was successfully stabilized by GO.…”
Section: Resultsmentioning
confidence: 98%
“…GO was selected because of previous work demonstrating its effectiveness for stabilizing oil-in-water emulsions. [20][21][22][23][24] Optical microscopy images of the emulsion before polymerization are provided in Fig. S1 † and demonstrate that the interface between the dispersed and continuous phases was successfully stabilized by GO.…”
Section: Resultsmentioning
confidence: 98%
“…Our previous work showed that PAO itself worked well to sequester nonpolar contaminants by liquid−liquid extraction. 37,38 That work also showed that a functionalized PIBbound additive (PIB 450 -catechol) facilitated the sequestration of hydrogen bond-accepting contaminants. We hypothesized that PIB oligomers functionalized with hydrogen bondaccepting groups such as amines could similarly be useful for the targeted removal of hydrogen bond-donating water contaminants such as phenols.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our recent work showed that poly­(α-olefin)­s (PAOs) could serve as recyclable extraction solvents for removal of trace amounts of nonpolar organic compounds from water in liquid/liquid extractions and in biphasic extractions using PAOs that were encapsulated within a polyurea shell. In these applications, PAOs do not contaminate the aqueous phase during mixing of the PAO and aqueous phases. In these systems, the PAO phases quantitatively separate from the cleaned aqueous phase by gravity separation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Landfester and colleagues prepared glycerol-encapsulated nanocapsules through interfacial polyaddition of glycerol and toluene diisocyanate using an oil-in-water emulsion stabilized by polyglycerol polyricinoleate, where the capsules can be used for improving the lubricant performance in metal–metal contact cases . Additionally, the Pentzer group constructed capsules from Pickering emulsions stabilized by 2D particles using interfacial polymerization between diisocyanate and diamine in oil/water, oil/oil, IL/water, and IL/oil systems, with the identity of the two phases dependent on the nanosheet functionalization. Using these systems, Luo et al and Edgehouse et al produced capsules with composite shells of polyurea and nanosheets and cores of IL or polyalpholefin for use in CO 2 uptake , and benzene removal from water, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Pentzer group constructed capsules from Pickering emulsions stabilized by 2D particles using interfacial polymerization between diisocyanate and diamine in oil/water, oil/oil, IL/water, and IL/oil systems, with the identity of the two phases dependent on the nanosheet functionalization. Using these systems, Luo et al and Edgehouse et al produced capsules with composite shells of polyurea and nanosheets and cores of IL or polyalpholefin for use in CO 2 uptake , and benzene removal from water, respectively. The ability to tailor not only the composition of the shell and core of the capsules but also their responsiveness to external stimuli will have broad impact across many fields.…”
Section: Introductionmentioning
confidence: 99%